Cap Testing at the Minntac Mine - Jack Eloranta (International Society of Explosives Engineers, 1992)
To improve control of blasting, tests were performed to assess non-electric cap accuracy. Simultaneous testing using a Velocity of Detonation Recorder (VODR), Red Lake LoCam and an Instantel DS-677 blast monitor was done. Favorable comparisons were found in the three records. This testing confirmed the accuracy of an inexpensive and expedient cap testing procedure.